Pengembangan Media Pembelajaran Augmented Reality pada Mata Pelajaran Informatika - Dicky Pujakesuma; Aryo Pinandito; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Merdeka curriculum requires students to explore more knowledge including basic subjects in technology, namely informatics. Informatics subject is a compulsory subject in all class X. Existing facilities are not sufficient to support practicum activities in this subject. One of the technologies that can be used as learning media to overcome these problems is Augmented reality. This technology really helps users to obtain, process, and remember information. Educational institutions that use the latest technology in the learning process will provide more experience than conventional learning processes, including for students who have inadequate skills and cognitive backgrounds. Augmented reality has the opportunity to be able to attract, motivate, inspire, explore, and be able to control from different perspectives so that students can see 3D objects without reducing the practicum experience. The research design in this research is implementative-development and the method of developing this learning media uses the waterfall which is considered effective for the development of small-scale learning media.testing black box obtained 100% function and meet the functional requirements that have been analyzed. The media expert test results obtained a value of 91.875% and material experts obtained 84% which means that this learning media is very feasible to use. The Cohen Kappa calculation shows that the appointed experts carry out the tests consistently and objectively.